Beginner students' perceptions of Youtube as a medium for learning basic vocabulary at English for Everyone - Muslihatun Muslihatun; Mega Mulianing Maharani (Indonesian Journal of Education and Pedagogy, 2026)
YouTube has become one of the most popular media platforms for informal learning, as digital technology has significantly transformed the way English is taught and learned.  The objective of the research is to find out how beginner students perceive using YouTube to learn basic English vocabulary, especially in the non-formal environment of the "English for Everyone" (EFE) program. The study used a quantitative method and a closed-ended questionnaire, which was adapted from Saputra (2022). The questionnaire consisted of ten statements and a four-point Likert scale (Strongly Disagree, Disagree, Agree, and Strongly Agree). There were twenty beginner-level students from the “English for Everyone” course who took part in the study. Descriptive statistics were applied to identify trends in students' perceptions about comfort, video support, motivation, convenience of use, and the effectiveness of YouTube for learning basic vocabulary. The results showed that most participants (95%) perceived YouTube as a fun and helpful tool for learning basic vocabulary. Many of the students enjoyed learning new words on YouTube and were inspired to keep going in their studies. The visual and audio elements of the videos improved student memory of words, and many beginner students claimed that repeating the videos can enhance their vocabulary recall. Beginner students also shown increased comfort in utilizing the new vocabulary they had studied. These results indicate that YouTube is a valuable and efficient tool for facilitating developing vocabulary, particularly in informal learning contexts such as English for Everyone (EFE).